Identidades profesionales y escritura de narraciones (auto)biográficas en el ingreso a la universidad. - Bombini, Gustavo; Iturrioz, Paola (Enunciación)
In this work we address the question of the production of professional identities in students entering the career of Language and Literature at the National University of San Martín (Argentina) from a corpus of writings produced as the final activity of one of the modules of the course income (2018, 19, 20). The entry to writing in the academic field from text that recognize an autobiographical bias are proposed as enablers of writing practices when questioning the deficient view of the legal practices of university entrants. (Bombini, Labeur, 2017) The perspective of analysis chosen by virtue of its productivity to recognize the close articulations between theory and practice, is the one offered by ethnography of education that in the line of the Mexican researcher Elsie Rockwell and the CINVESTAV team (Rockwell, 2009, 2018) has in some cases taken as an object of analysis the written culture and its fields of circulation, especially educational institutions. From the reading of the texts, dimensions of analysis emerged referring to family, neighborhood and community socializations, previous cultural and school experiences, representations that anticipate ideas and valuations about the academic field, diverse aesthetic choices, nucleus of interests, fantasies of intervention for transformation in the educational, cultural, political and linguistic-literary fields and, more specifically, expectations about the content of teacher education in language and literature.